Pengaruh Kepercayaan dan Persepsi Resiko terhadap Keputusan Pembelian Shopee di Sampang - M. Fayumi Makhdum; Siti Aminah (Universitas Batanghari Jambi, 2022)
This study aims to analyze and examine the effect of trust and risk perception on purchasing decisions. The population of this study are consumers in Sampang who have shopped at the Shopee Marketplace. The sample of this study was determined using purposive sampling so as to produce 63 respondents. The results in this study indicate that trust is able to make a positive contribution to purchasing decisions for shopee users in Sampang Regency. The perception of risk makes a positive contribution to the purchasing decisions of Shopee users in Sampang district.